Workshop of Assessment Development in Curriculum Merdeka : Pelatihan Pengembangan Asesmen pada Kurikulum Merdeka - Hindriana, Anna Fitri; Abidin, Zaenal; Setiawati, Ina (Yayasan Ahmar Cendekia Indonesia, 2024)
Implementation of Curriculum Merdeka involves a shift in teachers’ mindset on assessment development which orientates to facilitating Students development of learning. For that reason, the development of assesment instrument requires abilities to determine assessment method in accordance with indicator of achievement standard in cognitive, psychomotor, and affective domains. Considering the demand of the Curriculum Merdeka, the aim of this social service program is to train and assist teachers to develop assessment following the needs of the curriculum. The aim of program will be realised as a workshop for determining assessment method in Curriculum Merdeka and creating assessment rubric for cognitive, psychomotor and affective aspects. The output of the program shows an increase in teachers’ understanding about choosing the proper assessment method as well as an increase in the quality of assessment rubric leading to proper assessment of students learning development. Abstrak Implementasi kurikulum merdeka memerlukan perubahan mindset guru dalam mengembangkan asesmen yang dapat memfasilitasi perkembangan belajar peserta didik. Pengembangan instrumen penilaian memerlukan pemahaman yang mendalam terutama dalam menentukan metode penilaian yang sesuai dengan indikator capaian pembelajaran baik pada aspek pengetahuan, keterampilan dan sikap. Tujuan pengabdian pada masyarakat ini adalah untuk memberikanpengetahuan dan pendampingan dalam mengembangkan asesmen pada kurikulum merdeka. Metode dalam kegiatan ini adalah pelatihan penentuan metode asesmen dalam kurikulum merdeka dan pendampingan pembuatan rubrik penilaian untuk aspek pengetahuan, keterampilan dan sikap. Hasil pelatihan menunjukan adanya peningkatan pemahaman guru dalam memilih metode asesmen yang tepat sesuai dengan capaian pembelajaran dan proses pembelajaran, serta kualitas rubrik penilaian yang dapat menilai perkebangan belajar peserta didik.